Organic Light‐Emitting Diodes: Achieving Nearly 30% External Quantum Efficiency for Orange–Red Organic Light Emitting Diodes by Employing Thermally Activated Delayed Fluorescence Emitters Composed of 1, 8‐Naphthalimide‐Acridine Hybrids (Adv. Mater. 5/2018). Issue 5 (1st February 2018) - Zeng, Weixuan; Lai, Hsin‐Yu; Lee, Wei‐Kai; Jiao, Min; Shiu, Yi‐Jiun; Zhong, Cheng; Gong, Shaolong; Zhou, Tao; Xie, Guohua; Sarma, Monima; Wong, Ken‐Tsung; Wu, Chung‐Chih; et al.
Abstract : In article number1704961, Shaolong Gong, Chung‐Chih Wu, Chuluo Yang, and co‐workers present orange‐red organic light‐emitting diodes (OLEDs) with external quantum efficiencies of up to 29.2% through employing thermally activated delayed fluorescence emitters of a 1, 8‐naphthalimide–acridine hybrid. The relatively high photoluminescence quantum yield and horizontally oriented emitting dipoles of these emitters combined with the influence of the microcavity effect are verified to support the record‐high efficiency.